DIAGNOSIS OF OLTC USING DGA AND STATIC WINDING RESISTANCE TEST - Ahmad Khiar, Mohd Shahril; Md Thayoob, Yasmin Hanum; Yang Ghazali, Young Zaidey; Ab Ghani, Sharin; Sutan Chairul, Imran (2012)
On Load Tap Changer (OLTC) failure occurs is due to the insulation degradation and contacts failure inside it. Other than that, contacts wear influences the OLTC performances. The worn contacts will cause hotspots in the OLTC tank and cause the insulating oil to degrade faster. As a result, this will lead to the damage of complete transformer unit. Thus, the research work that has been carried out applied the Dissolved Gas Analysis (DGA) via latest Duval Triangle method during the diagnosis of OLTC rated at 33/11kV, 30MVA at the first stage to provide early indication of OLTCs breakdown. The Static Winding Resistance Test is then applied at the second stage to figure out any increase of contact resistances for all phases. In addition, it is expected to have a relationship between both results. The results showed that it was proven that by performing DGA via latest Duval Triangle method, the early indication of OLTCs breakdown can be obtained. Besides, this paper revealed that the Static Winding Resistance Test was capable to provide any sign of bad contacts in fixed condition as well as looses connections.